Abiotic and Microbial Interactions during Anaerobic Transformations of Fe(II) and NOX- - Picardal, Flynn (Frontiers in Microbiology, 2012)
Microbial Fe(II) oxidation using NO3- as the terminal electron acceptor [nitrate-dependent Fe(II) oxidation, NDFO] has been studied for over 15 years. Although there are reports of autotrophic isolates and stable enrichments, many of the bacteria capable of NDFO are known organotrophic NO3--reducers that require the presence of an organic, primary substrate, e.g., acetate, for significant amounts of Fe(II) oxidation. Although the thermodynamics of Fe(II) oxidation are favorable when coupled to either NO3- or NO2- reduction, the kinetics of abiotic Fe(II) oxidation by NO3- are relatively slow except under special conditions. NDFO is typically studied in batch cultures containing millimolar concentrations of Fe(II), NO3-, and the primary substrate. In such systems, NO2- is often observed to accumulate in culture media during Fe(II) oxidation. Compared to NO3-, abiotic reactions of biogenic NO2- and Fe(II) are relatively rapid. The kinetics and reaction pathways of Fe(II) oxidation by NO2- are strongly affected by medium composition and pH, reactant concentration, and the presence of Fe(II)-sorptive surfaces, e.g., Fe(III) oxyhydroxides and cellular surfaces. In batch cultures, the combination of abiotic and microbial Fe(II) oxidation can alter product distribution and, more importantly, results in the formation of intracellular precipitates and extracellular Fe(III) oxyhydroxide encrustations that apparently limit further cell growth and Fe(II) oxidation. Unless steps are taken to minimize or account for potential abiotic reactions, results of microbial NDFO studies can be obfuscated by artifacts of the chosen experimental conditions, the use of inappropriate analytical methods, and the resulting uncertainties about the relative importance of abiotic and microbial reactions. In this manuscript, abiotic reactions of NO3- and NO2- with aqueous Fe2+, chelated Fe(II), and solid-phase Fe(II) are reviewed along with factors that can influence overall NDFO reaction rates in microbial systems. In addition, the use of low substrate concentrations, continuous-flow systems, and experimental protocols that minimize experimental artifacts and reduce the potential for under- or overestimation of microbial NDFO rates are discussed.